A population - based study on Awareness of Cardiovascular Disease Risk Factors - George, Chinju; Andhuvan, G. (Indian Journal of Pharmacy Practice)
Objective: The study was to assess the level of Knowledge and Awareness of Cardiovascular Disease Risk Factors in a selected population. Materials and Methods: Population - based study was carried out in people above 30 years of age. Heart Disease Fact Questionnaire (HDFQ) was used to assess the level of knowledge and awareness of risk factors during face- to -face interview with the participants. Results: The percentage of participants who were aware about risk factors were 48% and 52% were unaware. Among risk factors, Over weight was ranked as the most common, followed by high cholesterol level (98%), high blood pressure (94%) and Smoking (92%).The participants were also aware about regular physical activity and exercise to lower risk factors for the heart disease. Conclusion: This study revealed the need for increasing awareness among the population utilizing community based education programs.
Keywords: Cardiovascular disease; risk factors; knowledge; awareness